Radon isotopes as tracers of climate-sensitive subsurface connectivity in Antarctic permafrost - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; C. Mazzoli; P. Tuccimei; G. Galli; L. Tositti; A. Zappi; J. Anderson; L. Davidson; et al. (Environmental Research, 2026)

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; M.C. Tartarello; C. Mazzoli; J.T.H. Anderson; V. Romano; R. Worthington; S. Bigi; R. Sassi; et al. (Science of The Total Environment, 2023)

Foreword - Francesco Sassi; Giorgio V. Dal Piaz; Carlo Doglioni (Rendiconti Lincei. Scienze Fisiche e Naturali, 2010)

Differences in the Crack Resistance of Interstitial, Osteonal and Trabecular Bone Tissue - L. P. Mullins; V. Sassi; P. E. McHugh; M. S. Bruzzi (Annals of Biomedical Engineering, 2009)

Miscellaneous isomorphous substitutions in Na-K white micas: a review, with special emphasis to metamorphic micas - Charles V. Guidotti; Francesco P. Sassi (Rendiconti Lincei. Scienze Fisiche e Naturali, 1998)